Odpowiedzi

2010-01-20T20:23:48+01:00
A) 3x+y=3
-x+2y= -8

y=3 - 3x
-x+2y = -8

podstawiamy w drugim równaniu za y
-x+2(3-3x)= -8

-x+6-6x=-8
-x-6x=-8-6
-7x=-14 |: -7
x= 2

podstawiamy do pierwszego równania
y=3-3*2
y=3-6
y=-3

rozwiazanie
x=2
y=-3

b)9x-3y=6
6x+y= -2

9x-3y=6
y=-2-6x
podstawiamy do pierwszego równania
9x-3(-2-6x)=6
9x+6+18x=6
9x+18x=6-6
27x=0
x=0
y=-2-6*0

x=0
y=-2
Najlepsza Odpowiedź!
2010-01-20T20:26:14+01:00
A) 3x+y=3
-x+2y= -8

y=3-3x
-x+2(3-3x)=-8

y=3-3x
-x+6-6x=-8

y=3-3x
-7x=-14

y=3-3x
x=2

y=3-3*2
x=2

y=3-6
x=2

y=-3
x=2


b) 9x-3y=6
6x+y=-2

9x-3y=6
y=-2-6x

9x-3(2-6x)=6
y=-2-6x

9x-6+18x=6
y=-2-6x

27x=0
y=-2-6x

x=0
y=-2-6*0

x=0
y=-2

2010-01-20T20:29:10+01:00
3x + y =3
-x +2y = -8

y=3-3x
-x + 2y =-8

y=3-3x
-x +2(3-3x) = -8

y=3-3x
-x +6-6x= -8

y=3-3x
-7x =-14

y=3-3x
x=2

y=3-6
x=2

y= -3
x= 2



****************

9x-3y=6
6x+y= -2

9x-3y = 6
y= -2 - 6x

9x-3(-2-6x) = 6
y= -2 - 6x

9x+6 + 18x = 6
y=-2 - 6x

27x=0
y=-2-6x

x=0
y=-2-o

x=0
y=-2


Myślę, że dobrze i czytelnie. Proszę o naj xD;)